Juridical Review of Construction Service Providers' Responsibilities for Failure to Construction of Village Roads according to Law Number 2 of 2017 Concerning Construction Services (Study on CV. Mabrur) - Muhammad Faizal Rifai; R Rizka (Proceeding International Conference Restructuring and Transforming Law, 2023)
Construction Services is a field that encourages increase in national development. But problems can arise in development failures. So from these problems the question arises, who is responsible for the consequences of the development failure, related to Law Number 2 of 2017 concerning Construction Services. The research conducted discussed the responsibility of construction service providers CV. Mabrur for the failure of the construction of the cast road belonging to Kebonsari Village as a user of construction services. This research method uses empirical juridical research methods, by conducting interviews with sources involved in this problem. So the results of what has been researched are proven to be errors or defaults that cause failure, namely the cracking of the cast road caused by a lack of solidity in the installation of the foundation on the cast road which ultimately causes losses to service users, therefore efforts are made to resolve it through negotiation channels to reach agreement or peace by both parties, CV. Mabrur as the construction service provider will be responsible for rebuilding the cracked part of the road.